(The effectiveness of the Bank Credit and its productivity in the Chadian economy: Chari Commercial Bank Case - (2008 / 2001 - Hassan, Mahamat Boukhari (Journal of Economic, Administrative and Legal Sciences, 2020)
This study aimed to investigate the extent to which Chari Commercial Bank contributed to the productivity of the Chadian economy through its credit, to identify the contribution of the commercial banks operating in Chad and their role in the productivity of the Chadian economy through their credit and also to identify the contribution of Chari Commercial Bank in the productivity of Chadian economy and total contribution of commercial banks in Chadian economy. Problem of the study: The problem of the study was to confirm the effectiveness of commercial banks in their contribution to finance projects and productivity in the Chadian economy, also to know the importance and effectiveness of commercial banks in the Chadian society. Can it be relied upon commercial banks to finance development to contribute to productivity in the Chadian economy? Researcher method: the researcher used mathematical method to calculate the compound growth rates of credit of Chari Commercial Bank, total bank credit and the national income of Chad during the period 2001-2008. Researcher also used the standard approach using the simple regression line equation to measure the contribution of both the Chari Commercial Bank and the total bank credit in Chadian economy. Findings: The results showed that bank credit is of great importance to contribute to the productivity of the economies of countries, so it can be relied upon to raise the rates of economic development. There is also positive relationship between the credit granted by the Chari Commercial Bank and the national income of Chad. The results proved that Chari Commercial Bank contributes effectively to productivity in the Chadian economy, where its contribution to bank credit reached 16% of total bank credit granted in Chad.